INFLUENCE OF p-CHLOROMERCURIBENZOATE ON THE ARGINASE ISOENZIMES OF RAT ORGANS IN THE PRESENCE OF NG-HYDROXIARGININE (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The influence of p-chloromercuribenzoate on rat liver, brain, and kidney arginase isoenzymes activity in the presence of intermediate compound NG-hydroxiarginine was investigated. It is shown that inhibition enhancement nonureothelic arginases of investigated organs by p-chloromercuribenzoate increases the influence of NG-hydroxiarginine. Liver ureothelic arginase does not react to the presence of p-chloromercuribenzoate and NG-hydroxiarginine.
Keywords: liver, brain, and kidney arginase; isoenzymes activity; p-chloromercuribenzoate